Xyloglucan endotransglucosylase/hydrolases (XTHs) are inactivated by binding to glass and cellulosic surfaces, and released in active form by a heat-stable polymer from cauliflower florets - Sharples, Sandra C (Journal of plant physiology, 2017)
Copyright © 2017 The Authors. Published by Elsevier GmbH.. All rights reserved.